Transformation of Islamic Education Management in Integrating Multiculturalism in Madrasah - Firmansyah, Firmansyah; Fridiyanto, Fridiyanto; Ningsih, Surya; Yaakob, Mohd Faiz Mohd (Idarah (Jurnal Pendidikan dan Kependidikan), 2025)
This study examines the integration of multiculturalism in Islamic schools and its impact on educational management, exploring how Islamic education can adapt to multicultural societies. The aim is to investigate the transformation of Islamic education management in integrating multiculturalism within Islamic school settings. This research utilizes a qualitative methodology incorporating comprehensive interviews, questionnaire, and observations from multiple Islamic educational institutions. The study indicates that diversity-supporting policies in Islamic educational settings cultivate inclusive learning environments, mitigate cultural conflicts, and deepen students' awareness of diverse backgrounds. This research provides valuable insights for educators, policymakers, and school administrators in Islamic educational contexts, particularly those operating in multicultural and diverse environments. The study contributes fresh perspectives on multicultural integration in Islamic schools, advancing understanding of how Islamic education can promote intercultural harmony. The research recommends expanding multicultural policies and enhancing teacher training programs to maximize the benefits of Islamic education that embraces multiculturalism, which strengthens intercultural relationships within school communities.